Nilai-Nilai Kearifan Lokal Sarung Tenun Samarinda: Studi Potensi Ekonomi Kreatif Perempuan Samarinda dalam Perspektif Ekonomi Islam - Darmawati, Darmawati (Jurnal Iqtisaduna, 2023)
Samarinda’s woven sarongs, which are rich in various patterns or motifs, make the cloth attract the attention of many tourists, from local to foreign tourists who visit the city of Samarinda, East Kalimantan. Coupled with the launch of the Samarinda Weaving Village by the chairman of Dekranas and the Governor of East Kalimantan, visitor traffic increased. This is because, from this woven culture, there are many lessons that can be drawn, starting from its cultural values to how this woven sarong will accommodate a large number of workers who can improve the welfare of the city. This study uses a qualitative research method, in which the source will be obtained through the field media, namely going directly to the place to conduct interviews with several women who empower Samarinda woven sarongs. The place where the research will be carried out is Samarinda Weaving Village, which is located on Jalan Pangeran Bendahara, Samarinda Seberang sub-district. Sampling was carried out by purposive sampling in the form of 4 (person) respondents from Samarinda sarong weavers who live in the Weaving Village, Samarinda City. Apart from that, documentation studies will also be used on published reports from previous studies. From the entire process, research results were found in two perspectives, namely the local wisdom value of the Samarinda woven sarong and the creative economic potential of the Samarinda woven sarong economy. The value of local wisdom lies in the selling value of Samarinda’s woven fabric which will increase/increase when socio-cultural functions are optimized. While the potential for the creative economy, this can advance the economy among women in order to get additional income. This is because the potential for this woven sarong is not only used as a sarong, but can be processed into a variety of other items ranging from suits, bags, or can be used as souvenirs at various Samarinda events. And from this it can also improve the economy of the Samarinda city.